Observation and Parameterization of Broadband Sea Surface Albedo. Issue 7 (2nd July 2019) - Huang, Chuan Jiang; Qiao, Fangli; Chen, Siyu; Xue, Yuhuan; Guo, Jingsong
Abstract: The broadband sea surface albedo (SSA) was observed from a fixed sea platform in the South China Sea. This observation period lasted approximately 152 days and included a wide range of atmospheric and oceanic conditions. Under clear‐sky conditions, the observed SSA increased significantly with the increase in the solar zenith angle at low solar altitudes, while the SSA changed little under high Sun. Under cloudy skies, however, the SSA was negligibly dependent on the solar zenith angle. The observed SSA was also influenced by atmospheric and oceanic conditions, in which it increased with increasing winds or surface waves and decreased with increasing water vapor pressure at the sea surface. An empirical parameterization of the broadband SSA was proposed based on these observations, in which the SSA was a function of the solar zenith angle, wind speed or significant wave height, and water vapor pressure. The correlation coefficients between the predicted SSA and the observations reached 0.95, 0.94, and 0.88 in clear skies, mixed skies, and cloudy skies, respectively. Finally, the root‐mean‐square deviations were only 0.009, 0.015, and 0.011 in these three sky conditions, respectively. Key Points: In clear skies, albedo increases with zenith angle at low Sun; albedo is independent of zenith angle in cloudy skies Albedo increases with winds or surface waves, while albedo decreases with an increase in water vapor at the sea surface An empirical albedo scheme was proposed, it was dependent on the solar zenith angle, wind speed/wave height, and water vapor pressure